2008
DOI: 10.1189/jlb.0807525
|View full text |Cite
|
Sign up to set email alerts
|

Maturing dendritic cells are an important source of IL-29 and IL-20 that may cooperatively increase the innate immunity of keratinocytes

Abstract: IL-19, IL-20, IL-22, IL-24, IL-26, IL-28, and IL-29 are new members of the IL-10 interferon family. Monocytes are well-known sources of IL-19, IL-20, and IL-24. We demonstrated here that monocytes also expressed IL-29, and monocyte differentiation into macrophages (Mphi) or dendritic cells (DCs) strongly changed their production capacity of these cytokines. Maturation of DCs with bacterial stimuli induced high expression of IL-28/IL-29 and IL-20. Simulated T cell interaction and inflammatory cytokines induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
113
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(125 citation statements)
references
References 52 publications
8
113
2
2
Order By: Relevance
“…Here, we show that in addition to MDDCs, IFN-1 expression is significantly induced in the human M-CSF-and GM-CSFderived macrophages (MPHs) (10 5 -and 10 4 -fold, respectively) (17) (Fig. S1 A), contrary to a previous study (16). The mRNA expression peaked at Ϸ2 h after LPS induction ( Fig.…”
Section: Distal Regulatory Elements Are Required For Lps-induced Exprcontrasting
confidence: 62%
See 1 more Smart Citation
“…Here, we show that in addition to MDDCs, IFN-1 expression is significantly induced in the human M-CSF-and GM-CSFderived macrophages (MPHs) (10 5 -and 10 4 -fold, respectively) (17) (Fig. S1 A), contrary to a previous study (16). The mRNA expression peaked at Ϸ2 h after LPS induction ( Fig.…”
Section: Distal Regulatory Elements Are Required For Lps-induced Exprcontrasting
confidence: 62%
“…Previous studies demonstrated that LPS-induced differentiation of MDDCs result in the rapid and robust expression of the IFN-1 gene (16). Here, we show that in addition to MDDCs, IFN-1 expression is significantly induced in the human M-CSF-and GM-CSFderived macrophages (MPHs) (10 5 -and 10 4 -fold, respectively) (17) (Fig.…”
Section: Distal Regulatory Elements Are Required For Lps-induced Exprmentioning
confidence: 54%
“…Expression of the IL-20R1/IL-20R2 and IL-22R1/IL-20R2 heterodimers, which are required for IL-20 bioactivity, have been observed only on cells of epithelial origin including skin, lung, and testis (1,18,19). These data suggest a major role for IL-20 SFCs in mediating cross-talk between infiltrating immune cells (T cells, macrophages, and dendritic cells) that express the IL20SFCs, and the skin.…”
mentioning
confidence: 97%
“…In contrast to IL-22, which is mainly produced by TH17, NK, and NK-like cells, IL-20 is mainly a monocyte and dendritic cell product, like IL-19 [9,69]. Bacterial LPS also induces IL-20 expression in glial cells in the brain [70].…”
Section: Il-20mentioning
confidence: 99%